Analysis and interpretation of the leaching behaviour of waste thermal treatment bottom ash by batch and column tests. (October 2016) - Di Gianfilippo, Martina; Costa, Giulia; Verginelli, Iason; Gavasci, Renato; Lombardi, Francesco
Highlights: Leaching as a function of L/S and pH assessed by batch and column tests. Lower release from RDF gasification BA due vitreous characteristics. For all BAs up to 10 fold differences for batch and column test results. Column tests suitable for constituents with availability-controlled release. pH-dependence tests suitable for constituents with solubility-controlled release. Abstract: This paper investigates the leaching behaviour of specific types of waste thermal treatment bottom ash (BA) as a function of both pH and the liquid-to-solid ratio (L/S). Specifically, column percolation tests and different types of batch tests (including pH-dependence) were applied to BA produced by hospital waste incineration (HW-I), Refuse Derived Fuel (RDF) gasification (RDF-G) and RDF incineration (RDF-I). The results of these tests were interpreted applying an integrated graphical and modelling approach aimed at identifying the main mechanisms (solubility, availability or time-controlled dissolution and diffusion) governing the release of specific constituents from each type of BA. The final aim of this work was in fact to gain insight on the information that can be provided by the leaching tests applied, and hence on which ones may be more suitable to apply for assessing the leaching concentrations expected in the field. The results of the leaching tests showed that the three samples of analysed BA presented differences of orders of magnitude in their leaching behaviour, especially as a function of pH, but also in terms of the L/S. These were mainly related to the differences in mineralogy of the samples. In addition, for the same type of bottom ash, the comparison between the results of batch and percolation column tests, expressed in terms of cumulative release, showed that for some constituents ( e.g. Mg for HW-I BA and Cu for RDF-G BA) differences of over one order of magnitude were obtained due to variations in pH and DOC release. Similarly, the eluate concentrations observed in the percolation tests, for most of the investigated elements, were not directly comparable with the results of the pH-dependence tests. In particular, in some cases the percolation test results showed eluate concentrations of some constituents ( e.g. K and Ca in HW-I BA) of up to one order of magnitude higher than the values obtained from the pH-dependence experiments at the same pH value. This was attributed to a rapid washout from the column of the soluble phases present in the BA. In contrast, for other constituents ( e.g. Mg and Ba for the RDF-G BA), especially at high L/S ratios, the concentrations in the column tests were of up to one order of magnitude lower than the solubility value, indicating release under non-equilibrium conditions. In these cases, batch pH-dependence tests should be preferred, since column tests results could underestimate the concentrations expected in the field.